DI-035 Should we make patients and nurses aware of their drug administration problems and training needs?. (24th March 2015) - Lampert, A; Haefeli, WE; Seidling, HM
Abstract : Background: Medicines administration errors are a well-known safety risk for patients and a lack of knowledge is one major cause of errors. Therefore, every effort is made to close knowledge gaps among medicine users to make drug administration safe. However, rarely the medicine users were prospectively asked for specific drug administration problems and training needs. Purpose: The first step in preventing errors is to study their aetiology. Therefore, we qualitatively assessed the medicine users' drug administration problems in order to investigate causes of errors and training needs. Material and methods: Focus groups with patients, caring relatives, and nurses were conducted using semi-structured interview guides for a focused exploration of participants' drug administration experiences and training needs. All discussions were audiotaped and videotaped. After verbatim transcription, data were analysed using Mayring's qualitative content analysis. Ethical approval was obtained from the local ethics committee and informed consent was signed by all participants prior to the study. Results: We conducted three focus groups with eleven patients and caring relatives, two focus groups with ten nurses from a nursing home, and one focus group with four nurses from a university hospital. In accordance with the published literature, patients and nurses reported drug administration problems related to different dosage forms, and potentially at every step in the administration process. The qualitative content analysis revealed that patients frequently trivialised drug administration, were unaware of errors, and primarily blamed the dosage form for administration problems. In contrast, nurses also sought out the patient as potential causes of administration problems e.g. due to dysphagia. Conclusion: Patients who are unaware of problems will not ask for help, and hence might not be reached by a traditional educational intervention. For the implementation and evaluation of the success of an educational intervention it is crucial to ask the intended target group, i.e. medicine users, for training needs. References and/or acknowledgements: Conflict of interest.